К вопросу о некоторых паразитарных и инфекционных заболеваниях позвоночных животных Сахалина - Беньковский, Л.М.; Головина, Т.И.; Щербина, Р.Д. (Вестник зоологии, 1973)
The article deals with some cases of parasitic and infectious diseases in the Sakhalin sea trout, Lepus timidus L., Vulpes vulpes L. and Ursus arctos L. Some biometric data
of sick animals are considered.